Persepsi Mahasiswa Akuntansi Mengenai Tax Evasion - Triani, Merry; Lestari, Melati Pramudita; Prastetyo , Henri (Jurnal E-Bis, 2025)
This study aims to determine the influence of fairness, taxation system, and discrimination on students' perceptions of tax evasion. The research background is the high incidence of tax evasion cases in Indonesia, which hinders state revenue. The research method employs a quantitative approach with data collection through questionnaires. The research sample consists of 6th and 8th-semester students of the D4 Accounting study program at Pontianak State Polytechnic. Data analysis uses multiple linear regression. The results show that fairness and discrimination do not significantly influence students' perceptions of tax evasion, while the taxation system has a significant effect. These findings indicate that a sound taxation system can reduce the perception that tax evasion is an ethical action. This research contributes to efforts to improve tax compliance through enhancements in the taxation system.